Reduction of retinal vessel density in non-exudative macular neovascularization: a retrospective study - Gao, Yang; Zhang, Su; Zhao, Yue; Yang, Tingting; Moreira, Paulo; Sun, Guangli (Frontiers in Medicine, 2024)
Purpose. To identify predictive activation biomarkers in retinal microvascular characteristics of nonexudative MNV, to avoid delay treatment or overtreatment of subclinical MNV. The main objective is to contribute to the international debate on a new understanding on the role of retinal vessel features in the pathogenesis and progression of nonexudative macular neovascularization (MNV) and age-related macular degeneration (AMD). A discussion on revising related clinical protocols is presented.In this retrospective study, the authors included eyes with nonexudative MNV, eyes with exudative AMD and normal eyes of age-matched healthy subjects respectively. The parameters were obtained by optical coherence tomography (OCT) and optical coherence tomography angiography (OCTA).Results. Twenty-one eyes with exudative AMD, 21 eyes with nonexudative MNV and 20 eyes of 20 age-matched healthy subjects without retinal pathology were included. Vessel density (VD) of the deep vascular complex (DVC) in eyes with nonexudative MNV was significantly greater than that in eyes with exudative AMD (P=0.002); while for superficial vascular plexus (SVP) metrics, no VD differences among sectors were observed between eyes with nonexudative MNV and eyes with exudative AMD.The reduction of retinal vessel density, especially in the DVC, seems to be involved in or be accompanied by nonexudative MNV activation and should be closely monitored during follow-up visits in order to ensure prompt antiangiogenic therapy. A discussion on applicable clinical protocols is presented aiming to contribute to new insights into ophthalmology services development directed to this specific type of patients and diagnosis.